Potensi Aktivitas Antioksidan Ekstrak Metanol Daun Sunglai (Peronema canescens Jack.) - Nisa, Nahdia Khairun; Marliana, Eva; Erwin, Erwin (JURNAL ATOMIK, 2024)
Sungkai (Peronema canescens Jack.) is a plant that has the potential as an antioxidant. This research was conducted to determine the antioxidant activity of sungkai leaves. The method use is DPPH damping with vitamin C as a positive control. Methanol extract of sungkai left contains alkaloids, flavonoids, saponins, phenolics and tannins. The antioxidant activity (IC50) was 81,91 mg/L. Methanol extract of sungkai leaf has the potential to have antioxidant activity.